2011
DOI: 10.1111/j.1365-2966.2011.20101.x
|View full text |Cite
|
Sign up to set email alerts
|

The Galaxy Zoo survey for giant AGN-ionized clouds: past and present black hole accretion events

Abstract: Some active galactic nuclei (AGN) are surrounded by extended emission‐line regions (EELRs), which trace both the illumination pattern of escaping radiation and its history over the light travel time from the AGN to the gas. From a new set of such EELRs, we present evidence that the AGN in many Seyfert galaxies undergo luminous episodes 0.2–2  years in duration. Motivated by the discovery of the spectacular nebula known as Hanny’s Voorwerp, ionized by a powerful AGN which has apparently faded dramatically withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
215
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(237 citation statements)
references
References 69 publications
(92 reference statements)
22
215
0
Order By: Relevance
“…Using a citizen science campaign to search for candidate AGN-ionized extended emission-line regions (EELRs) in SDSS images, participants of the "Galaxy Zoo" project (Lintott et al 2008) identified J1430+1339 as having an interesting EELR morphology (Keel et al 2012; later confirmed by HST imaging; Keel et al 2014). Due to the loopshaped "handle" of emission-line gas extending ≈12 kpc to the northeast of the SDSS image, Keel et al (2012) nicknamed this galaxy the "Teacup" AGN (which is the name we will now use). The HST imaging also reveals that the "Teacup" AGN resides in a bulge-dominated galaxy, with shell-like features, indicative of previous merger activity (Keel et al 2014).…”
Section: J1430+1339: the "Teacup" Agnmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a citizen science campaign to search for candidate AGN-ionized extended emission-line regions (EELRs) in SDSS images, participants of the "Galaxy Zoo" project (Lintott et al 2008) identified J1430+1339 as having an interesting EELR morphology (Keel et al 2012; later confirmed by HST imaging; Keel et al 2014). Due to the loopshaped "handle" of emission-line gas extending ≈12 kpc to the northeast of the SDSS image, Keel et al (2012) nicknamed this galaxy the "Teacup" AGN (which is the name we will now use). The HST imaging also reveals that the "Teacup" AGN resides in a bulge-dominated galaxy, with shell-like features, indicative of previous merger activity (Keel et al 2014).…”
Section: J1430+1339: the "Teacup" Agnmentioning
confidence: 99%
“…In this pilot study, we combine high-resolution radio imaging and spatially resolved spectroscopy for one radio-quiet type 2 quasar, J1430+1339 (nicknamed the "Teacup AGN"; Keel et al 2012; see Section 2). This source is drawn from a larger sample of type 2 AGNs that host kiloparsec-scale ionized outflows (Harrison et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As given by Keel et al (2015), the sample of AGN we consider includes the eight systems from the Galaxy Zoo survey of giant ionized clouds (Keel et al 2012a) where a simple energy-budget estimate including the ionization requirements of the most distant emission line region, compared to the observed bolometric luminosity of the nuclei, showed a shortfall greater than about a factor 5. These include NGC 5252 with its well-documented set of ionization cones (Prieto & Freudling 1996, Morse et al 1998, and the large-scale double radio source hosts NGC 5972 (Véron-Cetty & Véron 2001) and Mkn 1498 (Röttgering et al 1996).…”
Section: Galaxy Samplementioning
confidence: 99%
“…Our estimates of the bolometric luminosity of the AGN, and hence the role of obscuration on the ionizing radiation, can be updated from Keel et al (2012a) using the more sensitive and higherresolution survey data from WISE (Wright et al 2010) in place of IRAS or Akari for the midinfrared region including 22 µ. WISE data show that much of the mid-and far-IR flux attributed initially to UGC 7342 at z = 0.047 comes instead from a background starburst system at z = 0.069 (as identified in Paper I).…”
Section: Wise Datamentioning
confidence: 99%
See 1 more Smart Citation